Phytochemical composition and antioxidant properties on bark of Litsea garciae - SITI ZALEHA, RADUAN; Muhammad Hamdi, Mahmood; QAMAR UDDIN, AHMED; ABDUL RAZAK, KASMURI; WAN MOHD AZIZI, WAN SULAIMAN; Muhammad Hamdi, Mahmood; MUHAMAD RUSDI, AHMAD RUSMILI; Md. Abdur, Rashid Mia; MOHD FAROOQ, SHAIKH (2021)
The plants of the Litsea genus are widely explored concerning their nutritional and medicinal purposes. The recent study investigated the antioxidant capabilities and phytochemical composition of Litsea garciae (LG) bark’s hexane, chloroform, methanol, and aqueous extracts. Antioxidant measurements were performed by determining the total phenolic content (TPC) and the total flavonoid content (TFC). Antioxidant capacities were assessed employing free radical scavenging (DPPH assay) and ferric reducing power (FRAP assay). The secondary metabolites composition was evaluated by Ultra-High-Performance Liquid Chromatography-Mass Spectrometry (UHPLC-MS) method. As a result, methanol extract was recorded to have the highest TPC value aligned with its positive appearance in phytochemical screening. Its antioxidant capacity indicated the least IC50. Results showed that the significant free radical scavenging activity was related to the presence of high phenolic content in the methanolic extract. UHPLC-MS analysis revealed significant variation in the secondary metabolites present in the methanol extract. The major phenolic compounds were found including N-trans-feruloyl-4-O-methyldopamine, N-cis-feruloyltyramine, epicatechin-(4beta->6)-epicatechin-(2beta->7,4beta->8)-epicatechin, 7-Hydroxy-3- (4-methoxyphenyl)-4-propyl-2H-1-benzopyran-2-one and 9-O-Methylneodunol. Overall, results have suggested LG bark to be a lead source for novel natural products possessing antioxidative potential.